2017
DOI: 10.3390/molecules22111900
|View full text |Cite
|
Sign up to set email alerts
|

9,10-Dihydrophenanthrene with Two Spiro(dibenzocycloheptatriene) Units: A Highly Strained Caged Hydrocarbon Exhibiting Reversible Electrochromic Behavior

Abstract: The title dispiro hydrocarbon 1 was designed as a new electrochromic material. This multiply clamped hexaphenylethane-type electron donor was prepared from 2,2′-diiodobiphenyl via biphenyl-2,2′-diylbis(dibenzotropylium) 22+ salt. X-ray analysis of 1 revealed a highly strained structure as reflected by an elongated “ethane” bond [bond length: 1.6665(17) Å] and nearly eclipsed conformation. The weakened bond was cleaved upon two-electron oxidation to regenerate the deeply colored dication 22+. The reversible int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Especially in 1c/2c,w e found the largest difference in potential of about 1.1 eV before and after photocyclization. This change can be explained as follows:( i) the through-bond interaction that causes an increasing in the HOMO level would be maximized by expansion of the C À Cs ingle bond [40,41] and (ii)t he coefficients in HOMO are located on the DBCHT unit and the elongated s-bond in 1,w hereas the coefficients are located on the acenaphthene,pyracene,ordihydropyracylene skeleton in 2 based on DFT calculations ( Figures S10 and S13). On the other hand, two-electron reduction peaks were found in the far cathodic region due to cleavage of the elongated C À Cb ond to give 3 2+ or 4 2+ (dyrex behavior).…”
Section: Resultsmentioning
confidence: 99%
“…Especially in 1c/2c,w e found the largest difference in potential of about 1.1 eV before and after photocyclization. This change can be explained as follows:( i) the through-bond interaction that causes an increasing in the HOMO level would be maximized by expansion of the C À Cs ingle bond [40,41] and (ii)t he coefficients in HOMO are located on the DBCHT unit and the elongated s-bond in 1,w hereas the coefficients are located on the acenaphthene,pyracene,ordihydropyracylene skeleton in 2 based on DFT calculations ( Figures S10 and S13). On the other hand, two-electron reduction peaks were found in the far cathodic region due to cleavage of the elongated C À Cb ond to give 3 2+ or 4 2+ (dyrex behavior).…”
Section: Resultsmentioning
confidence: 99%
“…Further computational details are available in Section 5 of the Supporting Information. It has also been previously suggested that cofacial xanthenyl π‐systems provide a stabilizing influence via through‐bond and through‐space interactions [39,40] . Dispersion interactions between xanthenyl moieties in 1 2 were calculated as described by Johnson and co‐workers [41] as implemented in Multiwfn v3.8 [42] .…”
Section: Resultsmentioning
confidence: 99%
“…describe the fabrication of various functional C x H y molecules that exhibit interesting redox behaviors, even though electrochromic devices have not been reported [108–110] . For example, they used two spiro(dibenzocycloheptatriene) units to synthesize 9,10‐dihydrophenanthrene and observed a color change (from colorless to red) associated with C−C bond cleavage after two‐electron oxidation [110] . At a negative potential, its dication could be reduced back to the neutral spiro‐compound.…”
Section: Cxhy Molecules In Organic Electronic Devicesmentioning
confidence: 99%